PERAN ASIAN PARLIAMENTARY ASSEMBLY DALAM MENDUKUNG SOLUSI DAMAI PALESTINA-ISRAEL - Simela Victor Muhamad (Jurnal Politica, 2017)
A peaceful solution to the Palestinian-Israeli conflict that has not yet been reached should be of international concern, including parliament. Asian Parliamentary Assembly (APA), as the inter-parliamentary organization of Asian countries, needs to take a role in supporting a peaceful solution to the Palestinian-Israeli conflict. APA’s role, in line with the concept of network diplomacy, is to strengthen diplomacy networks among MPs of APA countries, as well as with other MPs in international fora, aimed at safeguarding the Palestinian-Israeli peace process should be in progress and peace talks can be resumed. APA’s role was run through diplomatic activity in scope of the APA meetings and beyond APA forum, particularly in the inter-parliamentary forum. APA’s role, with its diplomatic network, is important to support the Palestinian-Israeli peace process, although it does not directly resolve the conflict. This paper discusses the role of APA.